2015
DOI: 10.1158/0008-5472.can-15-0287
|View full text |Cite
|
Sign up to set email alerts
|

Network-Based Approaches to Understand the Roles of miR-200 and Other microRNAs in Cancer

Abstract: microRNAs (miRNA) are well suited to the task of regulating gene expression networks, because any given miRNA has the capacity to target dozens, if not hundreds, of genes. The simultaneous targeting of multiple genes within a pathway may enable miRNAs to more strongly regulate the pathway, or to achieve more subtle control through the targeting of distinct subnetworks of genes. Therefore, as our capacity to discover miRNA targets en masse increases, so must our consideration of the complex networks in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…The upregulation or downregulation of miRNAs levels found in several human cancers suggests that miRNAs may induce or inhibit tumorigenesis. miRNAs have been implicated in various cellular processes including cell proliferation, survival, apoptosis, migration, invasion and differentiation [29,30]. miR-509-5p has been implicated in cervical cancer and hepatocellular carcinoma, playing important roles in inhibition of tumorigenesis by abrogating cancer cell proliferation and invasion [18].…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation or downregulation of miRNAs levels found in several human cancers suggests that miRNAs may induce or inhibit tumorigenesis. miRNAs have been implicated in various cellular processes including cell proliferation, survival, apoptosis, migration, invasion and differentiation [29,30]. miR-509-5p has been implicated in cervical cancer and hepatocellular carcinoma, playing important roles in inhibition of tumorigenesis by abrogating cancer cell proliferation and invasion [18].…”
Section: Discussionmentioning
confidence: 99%
“…The miR-200 family is highly conserved and its roles in promoting the epithelial state and inhibiting EMT have been extensively studied (reviewed in Brabletz and Brabletz, 2010; Bracken et al, 2015; Gregory et al, 2008b; Hill et al, 2013) and were recently shown to be conserved in Drosophila (Antonello et al, 2015). Here we examine roles for miR-8 in the epithelium of the Drosophila wing in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In mammals the miR-200 family is made up of two genomic loci encoding microRNAs including miR-200a, miR-200b, miR-200c, miR-141, and miR-429. They are most strongly expressed in epithelial tissues, have similar seed regions with only one nucleotide difference generating two classes of target sites termed miR200a sites and miR200b sites, and can regulate overlapping targets involved in multiple signaling pathways (reviewed in Bracken et al, 2015). A key role for the miR-200 family in promoting the epithelial state has been shown, and high levels of miR-200 expression in mesenchymal cells can even promote a mesenchymal to epithelial transition (Gregory et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…A number of miRNAs act as tumor suppressor factors whereas others work in tumorigenesis (30). Among the miRNAs, the miR-200 family is proven to be directly associated with tumor metastasis and invasiveness (30)(31)(32). miR-200b, which is one of the members of the miR-200 family, has also been reported to have abnormal expression in various types of cancer, including bladder cancer and gastric carcinoma (33,34) PKCα belongs to the protein kinase C family and has been indicated to be involved in tumorigenesis, invasion, metastasis and proliferation (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%